Multidrug-resistant Escherichia coli and Klebsiella pneumoniae isolated from hospital sewage flowing through community sewage system and discharging into the Indian Ocean - Nemganga Z. Seguni; Zuhura I. Kimera; Frank Msafiri; Fauster X. Mgaya; Agricola Joachim; Anthony Mwingwa; Mecky I. Matee (Bulletin of the National Research Centre, 2023)
Abstract Background Hospital sewage is a significant reservoir of antimicrobial-resistant pathogens and genes that pose a huge public health threat. In this study, we determined the occurrence of multidrug-resistant Escherichia coli and Klebsiella pneumoniae in sewage flowing from a referral hospital through the urban sewage system to the point of discharge in the Indian Ocean. Results A total of 400 sewage samples were collected, yielding 517 isolates. Of these, 32.3% (167/517) were from hospital sewage, while 67.7% (350/517) were from the community. E. coli was the most common isolate (44.5% (230/517)), followed by K. pneumoniae at 27.3% (141/517), and other gram-negative bacteria constituted 28.2% (146/517) of the isolates. Multidrug resistance (MDR) was seen in 80.9% (186/230) E. coli and 71.6% (101/141) K. pneumoniae. Of the MDR isolates, 27.2% (78/287) were resistant to four different classes of antibiotics, while 6.9% (20/287) exhibited resistance to eight classes. The most frequent MDR pattern was PEN/CEP/TET/QNL/SUL, seen in 14.2% (38/287) of the isolates. The isolation frequency of MDR E. coli and K. pneumoniae at different sampling sites was high, being 47.6% in hospital chambers, 62.0% in hospital ponds, 58.1% in the treated hospital wastewater, and 55.6% in the community stream draining into the Indian Ocean. Extended spectrum beta-lactamase production was observed in 40% (92/230) of E. coli and 36.2% (51/141) of K. pneumoniae isolates. Resistance to quinolones among E. coli was 54.8% (126/230) and was 39.7% in K. pneumoniae (56/141). Carbapenem resistance in E. coli was 39.6% (91/230), while among K. pneumoniae isolates was 32.6% (46/141). Conclusions We found high proportions of multidrug-resistant E. coli and K. pneumoniae in the wastewater flowing from the hospital through the community sewage system to the point where it enters the Indian Ocean. Biological treatment did not significantly reduce the proportion of resistant bacteria, posing a very serious public health threat. The release of these highly resistant pathogens into the Indian Ocean is of international concern.